APPLIED KNOWLEDGE, ATTITUDE AND APPLICATION OF BEHAVIOURAL GUIDANCE TECHNIQUES IN ROUTINE OPD PATIENTS WITH DENTAL PHOBIA - Dr. Rathi Rela; Dr. Sahana Karthik; Dr. Manisha Pathak; Dr. Vikas Chandra Pankaj; Dr. Ritesh Vatsa; Dr Himanshu Tomar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Dental fear and anxiety are thought to be the primary cause of dental neglect, which can have a negative impact on a person's oral health as well as their general health, including their psychological well-being and quality of life.The current trial's objectives included evaluating the options available for treating such patients, the expertise and understanding of dentists in handling dental fear and anxiety in adult participants, and identifying the need for more training.Methods: The 82 dentists who participated in the study completed a unique survey and questionnaire trial. The results were developed via statistical analysis of the collected data.Results: Of the dentists surveyed (n=51), 62.19% (n=51) agreed that individuals should be educated and motivated, whereas one respondent (1.21%) thought that muscular relaxation was largely unsuccessful. According to 56.09% (n=46) of dentists, the most successful method was music and less waiting time in the clinic. 4 dentists (4.87%) believe that spreading out therapy across several appointments is a highly ineffective strategy.Conclusion: Within its limitations, the study demonstrated that the use of several behaviour modification approaches can be successful in reducing adult patients' dental anxiety and fear.